Avaliação da composição corporal e da percepção de autoimagem em estudantes universitários do curso de Nutrição - AGUIAR, Celenia Raquel Monteiro de (2018)
Introduction: Body image is defined as the "image that the individual has in their mind about the size, structure, shape and contour of their own body, as well as the feelings about these characteristics and the parts that constitute it ". Body dissatisfaction is multidimensional and may be related in isolation or in conjunction with weight, body shape and appearance. Studies show that the inadequate and irregular eating behavior affects mainly female individuals and the prevalence of diseases related to this situation is greater in specific groups, such as university students, athletes and professionals with a certain collection and demand of a low body weight. Objective: To evaluate the body image and nutritional status of university students in the course of nutrition. Materials and methods: A cross - sectional study was carried out with 181 students of both sexes from the Bacabal - Maranhão School of Education. The presence and degree of dissatisfaction with body shape were evaluated by BSQ 34, another instrument used in this study was BFS. Anthropometric data: weight, height, BMI, CC, CQ, CB, MOAD and BAI. Results: Mean age of 23.1 ± 5.2 years, majority (89.5%) women. Most of those surveyed were eutrophic (66.9%) according to BMI, and no image perception disorder according to BSQ34. According to the BSF, 56 students had the silhouette represented by figure 4, however the figure most desired by 111 students was demonstrated by silhouette 3, (p value 0.000). Demonstrating the desire for weight loss of the majority, despite being represented by a silhouette eutrophic. Conclusion: Most (66.9%) eutrophic, according to BMI and without image disturbances (54.7%) according to BSQ 34. However, there is a trend of overweight and obese individuals presenting with image disorders.